Multi-Cloud Automation : A Strategic Approach to Cloud Infrastructure Management - Saili Krishna Maliye (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the evolution and impact of multi-cloud automation strategies in modern enterprise environments, supported by comprehensive industry research and case studies. Drawing from multiple industry reports, including Flexera’s 2024 State of the Cloud Report and PwC’s Cloud and AI Business Survey, the research reveals that 89% of enterprises now employ multi-cloud strategies, with the global multi-cloud management market projected to grow at a CAGR of 27.3% through 2030. The article analyzes key components of successful multi-cloud automation, including deployment automation, operational excellence through monitoring, and incident management, while providing detailed metrics on their effectiveness. Through examination of real-world implementations across retail, financial services, and SaaS sectors, the research demonstrates how organizations achieve significant improvements in operational efficiency, cost optimization, and business agility through comprehensive automation strategies.